2022
DOI: 10.1021/acs.chemrestox.2c00145
|View full text |Cite
|
Sign up to set email alerts
|

Increased Levels of the Acrolein Metabolite 3-Hydroxypropyl Mercapturic Acid in the Urine of e-Cigarette Users

Abstract: Carcinogen and toxicant uptake by e-cigarette users have not been fully evaluated. In the study reported here, we recruited 30 e-cigarette users, 63 nonsmokers, and 33 cigarette smokers who gave monthly urine samples over a period of 4–6 months. Their product use status was confirmed by measurements of exhaled CO, urinary total nicotine equivalents, cyanoethyl mercapturic acid (CEMA), and total 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanol. Urinary biomarkers of exposure to the carcinogens acrolein (3-hydroxyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 54 publications
1
6
0
Order By: Relevance
“…Undoubtedly, however, electronic smoking devices pose a serious threat to global health and are one of the current public health problems; it is growing at an accelerating pace and has become a public health emergency [ 41 , 42 ]. E-cigarette manufacturers convince consumers that electric smoking devices pose a lower health risk by reducing carcinogenic and harmful substances, however, the latest research indicates otherwise [ 41 , 42 , 43 , 44 ]. Heating the products in electronic cigarettes produces condensed carcinogenic hydrocarbons and products toxic to the human body.…”
Section: Acrolein and E-cigarettes—a Healthier Alternative?mentioning
confidence: 99%
See 1 more Smart Citation
“…Undoubtedly, however, electronic smoking devices pose a serious threat to global health and are one of the current public health problems; it is growing at an accelerating pace and has become a public health emergency [ 41 , 42 ]. E-cigarette manufacturers convince consumers that electric smoking devices pose a lower health risk by reducing carcinogenic and harmful substances, however, the latest research indicates otherwise [ 41 , 42 , 43 , 44 ]. Heating the products in electronic cigarettes produces condensed carcinogenic hydrocarbons and products toxic to the human body.…”
Section: Acrolein and E-cigarettes—a Healthier Alternative?mentioning
confidence: 99%
“…At the same time, however, it is worth noting that the observed level of the 3HPMA metabolite in the urine of electronic cigarette users was still very high, significantly higher than in the case of non-smokers. Although e-cigarettes are likely to be less carcinogenic than tobacco cigarettes, the study results indicate that e-cigarette users have an increased risk of exposure to acrolein compared to non-smokers and are still exposed to its harmful effects [ 41 , 43 , 54 ]. In addition, Cheng et al [ 44 ], in studies using buccal cells isolated from e-cigarette smokers, clearly indicate a significant increase in the level of a carcinogen acrolein-DNA adduct 8R/S-3-(2′-deoxyribos-1′-yl)-5,6,7,8-tetrahydro-8-hydroxypyrimido [1,2-a]purine-10-(3H)-one (γ-OH-Acr-dGuo) compared to non-smokers.…”
Section: Acrolein and E-cigarettes—a Healthier Alternative?mentioning
confidence: 99%
“…Previous studies have reported that cannabis smokers have elevated urinary biomarker levels for other combustion products such as polycyclic aromatic hydrocarbons and acrylamide . The elevated levels of metabolites 2 and 3 in e-cigarette users contrasts to what has been reported for other volatile organic chemicals such as benzene and acrylonitrile in which e-cigarette users tend to have levels comparable to those of nonsmokers . Acrolein biomarkers, on the other hand, are elevated in exclusive e-cigarette users. , …”
mentioning
confidence: 75%
“…41 The elevated levels of metabolites 2 and 3 in ecigarette users contrasts to what has been reported for other volatile organic chemicals such as benzene and acrylonitrile in which e-cigarette users tend to have levels comparable to those of nonsmokers. 42 Acrolein biomarkers, on the other hand, are elevated in exclusive e-cigarette users. 42,43 Since these metabolites are derived from the toxic metabolite of furan, BDA, they are also biomarkers of potential harm.…”
mentioning
confidence: 99%
See 1 more Smart Citation